Pengaruh Perencanaan Pajak, Tunneling Incentive, Good Corporate Governance Terhadap Tindakan Transfer Pricing Dengan Kualitas Audit Sebagai Pemoderasi - Anggraini, Feby Ayu; Yanti, Harti Budi (Syntax Literate, 2025)
This study aims to analyze the influence of tax planning, tunneling incentive, and good corporate governance on transfer pricing practices, with audit quality as a moderating variable. The research employs a quantitative approach using secondary data from manufacturing companies listed on the Indonesia Stock Exchange for the period 2020–2024. Data analysis was conducted through multiple linear regression and moderation tests. The results reveal that tax planning and tunneling incentive have a positive significant effect on transfer pricing, while good corporate governance has a negative significant effect. Audit quality significantly moderates the relationship between tax planning and transfer pricing but does not moderate the relationships between tunneling incentive or good corporate governance and transfer pricing. These findings support agency and stakeholder theories and highlight the importance of audit quality and corporate governance in controlling aggressive transfer pricing practices.